Consecutive Sessions of Rescue Balloon Aortic Valvuloplasty for Critical Aortic Valve Stenosis Followed by Successful Bridging to Trans-Catheter Aortic Valve Implantation - Liang, Kae-Woei (Acta Cardiol Sin, 2015)
Percutaneous balloon aortic valvuloplasty (BAV) was a rare procedure in catheterization laboratories because of its limited prognostic impact. The recent advent of transcatheter aortic valve implantation (TAVI) has led to a resurgence of BAV, opening the way to a new indication as a bridge to TAVI. Herein, we reported an 83-year-old man with critical aortic valve stenosis and pulmonary edema, who strongly declined surgical aortic valve replacement. He also lacked financial support or insurance reimbursement for TAVI. He received BAV for relief of syncope, pulmonary edema and impending respiratory failure 4 times within 4 years and was successfully bridged to TAVI after receiving charity aid funding from the hospital.